Analysis of Tourism Education to Promote Innovation in Gastronomy - Suwandi, Andreas; Fitriyani, Endah; Wulung, Shandra Rama Panji (Universitas Pendidikan Indonesia, 2021)
The organization of tourism education is now important for the administration of gastronomic tourism. Vocational High Schools in the field of food expertise have a significant role in the development and promotion of gastronomic tourism in Bandung. Bandung has various types of food and drinks. At present, there is no mapping of gastronomic education in Bandung. The purpose of this research is to monitor the gastronomic mapping through the role of providing education namely the Vocational High School, diploma, and bachelor’s degree in the promotion and promotion of gastronomic tourism in Bandung. The research method used through the qualitative collection with secondary data collection techniques in the form of documentary evidence. The analytical method uses content analysis and descriptive. The results showed that gastronomy education was classified into three levels, namely vocational high school, diploma, and bachelor's degree. This study also maps the distribution of gastronomic education through the role of tourism education to promote gastronomy in Bandung